2015
DOI: 10.1007/s13277-015-3227-3
|View full text |Cite
|
Sign up to set email alerts
|

Crucial microRNAs and genes of human primary breast cancer explored by microRNA-mRNA integrated analysis

Abstract: This study aimed to screen potential microRNAs (miRNAs) and genes related to human primary breast cancer. The gene and miRNA expression profile data of GSE19783 was obtained from Gene Expression Omnibus. The matched messenger RNA (mRNA) and miRNA expression profiles of 100 human primary breast cancer samples were chosen for further analysis. The miRNA-gene regulatory modules were screened via iterative multiplicative updating algorithm. The potential functions of genes in modules were predicted by functional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…MiRNAs have been reported as oncogenes, tumor suppressors, and regulators in numerous cancers, such as gastric cancer and breast cancer [Yang et al, ; Suarez‐Arriaga et al, ]. Similarly, we found that the expression of miR‐892a was up‐regulated in cancer tissues compared with the matched adjacent tissues.…”
Section: Discussionsupporting
confidence: 74%
“…MiRNAs have been reported as oncogenes, tumor suppressors, and regulators in numerous cancers, such as gastric cancer and breast cancer [Yang et al, ; Suarez‐Arriaga et al, ]. Similarly, we found that the expression of miR‐892a was up‐regulated in cancer tissues compared with the matched adjacent tissues.…”
Section: Discussionsupporting
confidence: 74%
“…SFRP1 is frequently downregulated in gliomas, but the cause of its downregulation is not well understood. Many investigators have reported that other miRNAs, such as miR-1260b, 127-3p, 206, and 139-5p, can inhibit cells' proliferation by targeting SFRP1 in prostate cancer, glioblastoma, gastric cancer, and breast cancer [24][25][26][27]. Other investigators showed that miR-1/206 regulates the SFRP1 gene and affects skeletal muscle development [28].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, increasing research on miRNA has emphasized the importance of miRNAs in gene regulation (18). miRNAs are a class of non-coding single-stranded small RNA nucleotides from pri-miRNA processing by Drosha and Dicer (19). Typically, miRNAs can recognize specific mRNAs, and bind to their 3'-UTR by inexact match, affecting mRNA stability, or inhibit their translation, regulating the expression levels of target genes (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%